The Effect of Feeding Frequency on Groth and Survival Rate of Keperas Fish (Pentius brevis) - Mulya Fitra; Komariyah, Siti; Laila Fitri (Fakultas Pertanian Universitas Samudra, 2022)
Keperas (Pentius brevis) is a fish that has important economic value and is in great demand among the people of Central Aceh. The population of keperas fish has begun to decrease due to the catch of the surrounding community, so efforts are needed to be cultivated. In cultivation activities, it is necessary to know the proper management of feeding, one of which is the frequency of feeding. The research design used in this study was RAL with 3 treatments and 3 repetitions. The treatments given were different feeding frequency (P1 = 2 times per day, P2 = 3 times per day and P3 = 4 times per day). Parameters observed included absolute length and mutlat weight growth, daily growth rate, feed efficiency and survival rate. Based on ANOVA, feeding frequency had a significant effect (P<0.05) on growth in length and absolute weight and feed efficiency, but had no significant effect (P>0.05) on daily growth rate and survival rate. The best treatment was produced by feeding 3 times per day (P2) because it produced the highest growth performance among other treatments